Differentiating spontaneous echo contrast, sludge, and thrombus in the left atrial appendage: Can ultrasound enhancing agents help?. Issue 7 (1st July 2019) - Posada‐Martinez, Edith Liliana; Trejo‐Paredes, Camila; Ortiz‐Leon, Xochitl A.; Ivey‐Miranda, Juan Betuel; Lin, Ben A.; McNamara, Robert L.; Arias‐Godinez, Jose Antonio; Lombo, Bernardo; Sugeng, Lissa
Abstract: The accurate identification of thrombus in the left atrial appendage with transesophageal echocardiogram (TEE) in patients with atrial fibrillation (AF) before cardioversion is essential. Most of these patients have some grade of spontaneous echo contrast (SEC). Severe SEC is often called "sludge, " and its prognosis and treatment are still controversial. Current guidelines suggest the use of ultrasound enhancing agents (UEAs) when significant SEC is present. However, little is known about the utility of the UEAs in the differentiation between sludge and less severe SEC.